Pengaruh Customer Orientation, Brand Commitment, Brand Risk Terhadap Brand Loyalty pada Merek Bumi Susu di Bogor - Nela Tri Istianti; Ika Baskara (IAI Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to determine the effect between customer orientation and brand loyalty through mediation of brand risk and brand commitment. Quantitative method using milk objects and a sample of 109 people in Bogor. The population covered includes Bumi Susu consumers in Bogor city/regency. The sampling technique used is non-probability sampling by taking purposive samples. Data processing was carried out using the Structural Equation Modeling (SEM) method to determine the direct effect of the relationship between customer orientation and brand loyalty and the indirect effect by looking at the relationship between customer orientation and brand loyalty through the mediation of brand risk and brand commitment. The results of this study show an insignificant relationship between customer orientation and brand loyalty but mediation of brand risk and brand commitment is done to connect customer orientation with brand loyalty. The indirect relationship with this mediation has a positive and significant effect. This research has managerial implications for businesses considering brand risk and brand commitment that can affect brand loyalty so that companies can survive in business competition. Brand loyalty is one of the factors that influence repeat purchases which will affect sales.